The study of the efficiency of anther culture in vitro of bread wheat varieties and hybrids (Triticum aestivum L.) - N. V. Petrash; Е. А. Orlova; I. Е. Likhenko; V. V. Piskarev (Зерновое хозяйство России)
Anther culture is the most effective and not technically complex tool for obtaining double wheat haploids. The current study is devoted to the research of the influence of the genotype and concentration of the growth regulator 2.4-D on the efficiency of androgenesis in vitro of spring bread wheat. The purpose of the study was to estimate the efficiency of the anther culture of hybrids of the first and second generation and their parental varieties and to study its dependence on different concentrations of the growth regulator 2.4-D. There has been carried out the estimation of the traits of the F1 hybrids, the F2 population, and the parental varieties ‘Obskaya 2’ and ‘Novosibirskaya 15’ when 2.4-D was added to the induction medium at a concentration of 1 and 2 mg/l. There has been established that the F2 population and the parental variety ‘Novosibirskaya 15’ are characterized by the largest indicators. The average values were significantly surpassed by the F2 population in the traits ‘number of productive anthers per 100 anthers’ and ‘number of all regenerants per 100 anthers’ at 1 mg/l of 2.4-D. The variety ‘Novosibirskaya 15’ surpassed the average values in traits ‘number of sprouts per 100 anthers’ and ‘number of all regenerants per 100 sprouts’ at 2 mg /l of 2.4-D. The trial has shown that the best responsiveness of the anther culture for the studied genotypes was when the growth regulator 2.4-D was added to the induction medium at a concentration of 1 mg/l. The variety ‘Novosibirskaya 15’ has been characterized by good responsiveness in anther culture in vitro and could be used as a donor of valuable alleles in wheat breeding programs using DH technologies.